Comparison between teams of different ranks in small-sided and conditioned games tournaments - Correia da Silva, D.; Teoldo da Costa, V.; Casanova, F.; Manuel Clemente, F.; Teoldo, I. (International Journal of Performance Analysis in Sport, 2019)
The aim of this study was to compare the quantity, the quality and the outcome of the tactical actions of the champions` teams compared to runner-up and third-placed teams in small-sided and conditioned games tournaments in the under-15 category. We analyzed 18 teams composed of three players, they were 13.92 ± 1.17 years old and with 5.65 ± 2.65 years of time practice. These players performed 4,716 tactical actions evaluated by System of Tactical Assessment in Soccer (FUT-SAT). Descriptive statistics (mean, standard deviation and percentage difference), Shapiro-Wilk test, independent t-test, Mann-Whitney test, paired t-test, and Cohen`s kappa test were used. The results indicated that the champions` teams accomplished more offensive tactical actions (quantitatively) and were more efficient (qualitatively) in these actions than the other teams. In addition, the champions` teams were more effectiveness (action outcomes) in offensive and defensive movements. Otherwise, the runner-up and third-placed performed more (quantitatively) defensive tactical actions and were more efficient (qualitatively) in these actions. It is concluded that the champions` teams had more initiative in the matches due to the greater quantity and quality of their offensive tactical actions and more effectiveness in the offensive and defensive actions, while their opponents were reactive.